Impact of Negative News on the U.S. Soft Drinks Industry - Bhattacharya, Abhi (Indian Journal of Finance, 2019)
The fact that negative news affects the stock returns of a mentioned brand is well known and proven extensively in literature. Nevertheless, little is known about the effect this might have on other brands within the industry in which the focal brand operates. This phenomenon was investigated by looking at the effect of negative news articles on similar and dissimilar competitors in the soft drink industry. Extent literature has theoretically posited that competitors may either benefit or share the harm depending on the presence of competitive or contagion effects. However, such effects have rarely been investigated empirically. Results generated through data from the soft drinks industry indicated that negative news in general lowered the stock returns of the focal brand active in the industry. Second, the effect of negative headlines had a significant effect on competitors but was competitor specific. Negative Coca-Cola headlines resulted in a contagion effect over the entire industry; negative Pepsi headlines resulted in competitive effects for both Coke and Dr Pepper; negative Dr Pepper headlines also resulted in contagion effects over the entire industry. These results hold important consequences for firm managers and stockholders.